Construction of the Evaluation Index System for Nurse Deployment Pertaining to the Disaster Rescue. (23rd June 2022) - Xu, Yue; Gao, Na; Li, Xiaoqian; Wang, Ping; Ren, Haoyuan; Pi, Hongying
Abstract : Based on the Delphi method, the analytic hierarchy process, and the entropy method, this paper constructs the evaluation index system for nurse deployment pertaining to the disaster rescue in military hospitals to furnish the reference evidence for scientific deployment of nursing staff, thereby promoting the rescue supportability. This paper establishes the expert consultation form of the evaluation index system for nurse deployment pertaining to the disaster rescue in military hospitals through expert interviews, group discussions, and so on. The Delphi method is applied to enquire 20 military experts in different professional fields two times, and the evaluation index system is finally determined. The weights of evaluation indexes of disaster rescue nurses are determined by the analytic hierarchy process and entropy method. The construction of the evaluation index system for the deployment of disaster relief nurses in military hospitals through Delphi method, analytic hierarchy process, and entropy method provides a reference method for rational allocation of nurses and points out the key points of hospital training. In addition, this paper provides a reference for the assessment and selection of nurses related to disaster relief in military hospitals and lays a foundation for the construction of subsequent evaluation models, which is of great significance for improving the level of nursing teams.